ANALYSIS OF FACTORS AFFECTING THE EFFECTIVENESS OF PERSONNEL MANAGEMENT (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The article examines scientific research conducted by foreign scientists, scientists from the Commonwealth of Independent States and Uzbek scientists on personnel management in industrial enterprises. The research methodology is presented. The types of factors influencing the effectiveness of personnel management are studied. The study examined the specifics of such factors as information and know-how, financial and material resources, human resources, internal communications and relationships. The features of personnel management in America and Japan are studied. Currently, many Western companies are working in three main areas of human resource management: full automation of production processes, improvement of forms and methods of business management, as well as training and advanced training of personnel. The content of physical, technical and technological, socio-economic, socio-psychological, territorial-contextual and innovative factors influencing personnel management is indicated.